METODE CAMPURAN ANALISIS KESALAHAN PADA PENULISAN TEKS DESKRIPTIF SISWA KELAS XI SAMA NEGERI 4 PADANGSIDIMPUAN - Diah Annur Achzuhrufi Harahap; Shoufi Nisma Dewi; Rahmat Huda; Arynayanty; Farhan Afif Al Kindi; Nasibah Awae (CV. Alfa Pustaka, 2026)
This research aims to investigate the specific types and frequency of linguistic errors found in the descriptive writing of eleventh-grade students at SMA Negeri 4 Padangsidimpuan. Utilizing a Sequential Explanatory mixed-methods design, the study combined quantitative data mapping with qualitative in-depth analysis. The sample consisted of 33 students chosen via purposive sampling. Data collection involved a descriptive writing test and a Likert-scale questionnaire. Analysis revealed 284 total errors across five distinct categories: capitalization, spelling, punctuation, part of speech, and sentence structure. Capitalization errors were the most prevalent at 61.38%, followed by spelling (22.77%), comma errors (8.91%), and full stop errors (6.93%). While sentence structure errors were relatively infrequent (12.37%), the overall mean score from the questionnaire was 3.29, suggesting that students find using parts of speech moderately challenging. The study concludes that the primary hurdles for students are mechanical conventions rather than core grammatical rules. Consequently, the researcher suggests that English teachers should focus more on revising and editing phases during the writing process to improve accuracy.